How to Destroy the Main Reservoir of HIV After Infection: New Medicine - Zajac, Vladimir (British Journal of Healthcare and Medical Research, 2024)
Every virus is a parasite that cannot exist on its own and is fully dependent on its host. This is the basic condition of its existence. It is fully dependent on the host and thus it is - a living cell. What kind of living cell? It was found that the carriers of BLV and the new coronavirus are commensal bacteria of the intestinal tract. HIV carriers are bacteria and yeasts of the intestinal and respiratory tract.